How CEO narcissism affects corporate social responsibility choice? - Chen, Jing; Zhang, Zhe; Jia, Ming (Asia Pacific journal of management, 2021)
This study aims to explore how CEO narcissism affects firms’ CSR choice given that the relationship between chief executive officer (CEO) narcissism and corporate social responsibility (CSR) has yielded inconclusive results. On the basis of upper echelon theory and the attention-based view, we first propose that narcissistic CEOs allocate more attention to peripheral CSR and less attention to embedded CSR. We then explore the boundary conditions that may affect CEO narcissism and CSR choice. We find that CEO narcissism is positively related to peripheral CSR and negatively related to embedded CSR via a sample of 4792 firm-year observations in the manufacturing industry of Chinese A-share listed firms. Results show that family ownership weakens the negative relation between CEO narcissism and embedded CSR. Moreover, CEO duality strengthens the positive relation between CEO narcissism and peripheral CSR and strengthens the negative relation between CEO narcissism and embedded CSR. These findings have significant implications for the CSR literature, narcissism research, and the attention-based view.